2017
DOI: 10.1111/are.13481
|View full text |Cite
|
Sign up to set email alerts
|

Molecular isolation and characterization of a haemocyanin ofMacrobrachium rosenbergiireveal its antibacterial activities

Abstract: Haemocyanin is a multi-subunit protein complex found in the haemolymph and is involved in the immune system of crustaceans. In this study, a haemocyanin gene of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Phylogenetic analysis revealed that Mr Hc2 is closely related to Hc‐1 of M. nipponense (92.49% identity; Kong et al 2016). However, Mr Hc2 exhibited only 61.55% identity with Mr Hc from M. rosenbergii in our previous study (Srisuk et al 2018). This evidence demonstrates the diversity of hemocyanin functions that descend from evolutionarily derived sequence variance.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Phylogenetic analysis revealed that Mr Hc2 is closely related to Hc‐1 of M. nipponense (92.49% identity; Kong et al 2016). However, Mr Hc2 exhibited only 61.55% identity with Mr Hc from M. rosenbergii in our previous study (Srisuk et al 2018). This evidence demonstrates the diversity of hemocyanin functions that descend from evolutionarily derived sequence variance.…”
Section: Discussionmentioning
confidence: 56%
“…In the present study, Mr Hc2 protein with a molecular mass of 77.3 kDa might correspond to the 78‐kDa subunit of Mr Hc4. The Mr Hc protein in our previous study, which had a molecular mass of 76.5 kDa, might correspond to the 76‐kDa subunit of Mr Hc4 (Srisuk et al 2018).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations